Validity and Reliability of The Indonesian Version of Patient Allergic Rhinitis Questionnaire and Allergic Rhinitis Prevalence in A Class Of 2018-2019 Medical Students of Universitas Padjadjaran, Indonesia - Sally Mahdiani; Sheila Rafifah Yuliantoputri; Melati Sudiro; Arif Dermawan; Lina Lasminingrum (International Journal of Integrated Health Sciences, 2022)
Objective: To determine the validity and reliability of the Indonesian version of Patient Allergic Rhinitis Questionnaire as a screening tool for AR and the prevalence of AR in a class of 2018-2019 medical students of Universitas Padjadjaran, Indonesia.Methods: A cross-sectional descriptive study was performed during the period November-December 2021 on a class of 2018-2019 medical students of Padjadjaran University. The Indonesian version of the pre-validated Patient Allergic Rhinitis Questionnaire was distributed online. Allergic rhinitis was determined from history taking by identifying a history of a previous diagnosis of AR and/or 2 or more symptoms (watery runny nose, sneezing, nasal congestion, itching, or conjunctivitis) for more than 1 hour on most days.Results:. The validity of the Indonesian version of the Patient Allergic Rhinitis Questionnaire was good with a 0.895 Cronbach's Alpha coefficient, reflecting a reliable questionnaire. The prevalence of AR was 35.8% with most were female (69.2%). There were 59.9% of respondents who had a history of allergy in their parents. The most common symptom was nasal congestion (85.7%) and the moderate-severe persistent (49.2%) was the most common ARIA-WHO classification. Dusty places (92.1%) were the most common cause of symptoms. The most common comorbidity was rhinosinusitis (35%). The mean symptom severity score was 6.7.Conclusions: The Indonesian version of the Patient Allergic Rhinitis Questionnaire is valid and reliable as a screening tool for AR. The prevalence of AR in this study is quite high, with moderate-severe persistent as the most prominent classification.